Sexual Transmission-Risk Behavior Among HIV-Positive Persons: A Multisite Study Using Social Action Theory. - Sullivan, Kathleen M; Rose, Carol Dawson; Phillips, J Craig; Holzemer, William L; Webel, Allison R; Nicholas, Patrice; Corless, Inge B; Kirksey, Kenn; Eller, Lucille Sanzero; Voss, Joachim; Tyer-Viola, Lynda; Portillo, Carmen; et al. (Journal of advanced nursing, 2016)
Sexual risk behavior was explored and described using Social Action Theory.